The Influence of Organizational Culture and Employee Engagement on Employee Performance with Job Satisfaction as a Mediating Variable (Case Study at PT. Alkautsar Cater Indonesia in Java Island) - Pebriyansyah, Nodi (Universitas Muhammadiyah Tangerang, 2025)
PT Alkautsar Cater Indonesia is a company specializing in catering and aqiqah services. It operates its own farm, providing goats and sheep sourced internally. Currently, PT Alkautsar Cater Indonesia has expanded its operations by establishing 17 branches. This research employed a census method, wherein all members of the population were included as the sample. The total sample comprised 105 employees of PT Alkautsar Cater Indonesia. The findings indicate that organizational culture and employee engagement significantly impact job satisfaction and employee performance. Furthermore, job satisfaction has been shown to serve as a mediating variable in the relationship between organizational culture and employee engagement on performance. Based on these findings, the author recommends that PT Alkautsar Cater Indonesia continue to support and strengthen its organizational culture while enhancing employee engagement to further boost job satisfaction and overall performance.Keywords: Organizational Culture, Employee Engagement, Job Satisfaction, Employee Performance